Unraveling the Potential of Baru (Dipteryx alata Vog.) Fruit Fractions as a Sustainable Food Ingredient: Chemical and Technological Characteristics and Prebiotic Potential - Sousa, Tainara Leal de; Filho, Josemar Gonçalves de Oliveira [UNESP]; Cabassa, Isabelly de Campos Carvalho; Lemes, Ailton Cesar; Egea, Mariana Buranelo (MDPI, 2024)
The baru is a native Brazilian Cerrado fruit known for its high nutritional and techno-functional value, with the potential to generate new food ingredients. Utilizing the entire baru fruit maximizes the use of all its components, reduces the environmental impact, minimizes waste, and contributes to the region’s sustainable development. In this context, this study aimed to evaluate the nutritional composition, bioactive compounds, technological properties, and prebiotic potential of baru by-products and nuts, aiming at their integral and sustainable utilization. For this purpose, baru fruits were collected, characterized in terms of biometrics, and separated into pericarp (by-product) and nuts. The nutritional composition, fatty acid profile, bioactive compounds, techno-functional properties, and prebiotic potential were characterized in the roasted almonds and the by-products. The results indicated that the baru meal had a high protein content (33.09 g/100 g), the lowest atherogenic and thrombogenic indices (0.09 and 0.10, respectively), and the highest antioxidant capacity in the DPPH, ABTS, and FRAP assays. Additionally, the baru meal showed high levels of potassium (14.05 g/100 g), magnesium (2.20 g/100 g), and iron (61.80 g/100 g). The mesocarp stood out for its higher total phenolic content (157.48 mg GAE/100 g) and enhanced water solubility (63.90 g/g). The baru almond flour showed the best results for water absorption capacity (3.62 g/g), oil absorption capacity (3.28 g/g), emulsifying activity (71.94%), emulsion stability (87.69%), and foaming capacity (8.17%). In terms of prebiotic activity, the endocarp fermented by Lactobacillus acidophilus (0.76 log CFU/mL) and the mesocarp fermented by Bifidobacterium animalis (0.62 log CFU/mL) presented the best results. These findings demonstrate that baru by-products have the potential for full utilization, contributing to the sustainable development of underexplored plant species.
Keywords: by-products; Cerrado; nutritional composition; prebiotic activity